1995
DOI: 10.1093/nar/23.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of mitochondria: strategy towards a gene therapy of mitochondrial DNA diseases

Abstract: Successes in classical gene therapies have been achieved by placing a corrected copy of a defective nuclear gene in cells. A similar gene replacement approach for a mutant mitochondrial genome is invariably linked to the use of a yet unavailable mitochondrial transfection vector. Here we show that DNA coupled covalently to a short mitochondrial leader peptide (chimera) can enter mitochondria via the protein import pathway, opening a new way for gene-, antisense-RNA- or antisense-DNA-delivery in molecular thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(74 citation statements)
references
References 46 publications
1
68
0
5
Order By: Relevance
“…Vestweber and Schatz, 28 however, were able to demonstrate that by subjecting import-competent, isolated mitochondria to DNA-conjugated mitochondrial precursor proteins, the DNA became nuclease or phosphodiesterase resistant, consistent with the mitochondria importing nucleic acids via the general protein import pathway. A similar observation was more recently reported by Seibel et al, 29 although their experiments involved a less direct analysis of the putatively imported DNA moiety. Our in vitro studies with isolated rat liver mitochondria now show that biotinylated PNAs can also be delivered across an intact mitochondrial membrane into the matrix compartment by the addition of a mitochondrial targeting peptide.…”
Section: Mitochondrial Targeting and Importsupporting
confidence: 87%
“…Vestweber and Schatz, 28 however, were able to demonstrate that by subjecting import-competent, isolated mitochondria to DNA-conjugated mitochondrial precursor proteins, the DNA became nuclease or phosphodiesterase resistant, consistent with the mitochondria importing nucleic acids via the general protein import pathway. A similar observation was more recently reported by Seibel et al, 29 although their experiments involved a less direct analysis of the putatively imported DNA moiety. Our in vitro studies with isolated rat liver mitochondria now show that biotinylated PNAs can also be delivered across an intact mitochondrial membrane into the matrix compartment by the addition of a mitochondrial targeting peptide.…”
Section: Mitochondrial Targeting and Importsupporting
confidence: 87%
“…This approach enables a range of small molecules to be targeted to mitochondria and extends and complements earlier approaches designed to target DNA and related molecules to mitochondria (39)(40)(41). For this strategy to have clinical potential, therapeutically effective concentrations of bioactive molecules must be delivered to mitochondria without toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports showed that the conjugation or direct modification of MTS permitted a macromolecule such as a protein, DNA and a liposomal nanocarrier to be delivered to mitochondria [8][9][10][11][12] . On the other hand, some researchers have reported the use of a mitochondrial RNA aptamer for mitochondrial delivery.…”
Section: Introductionmentioning
confidence: 99%